2017
DOI: 10.1002/ppul.23695
|View full text |Cite
|
Sign up to set email alerts
|

Filamin A (FLNA) mutation—A newcomer to the childhood interstitial lung disease (ChILD) classification

Abstract: The progressive nature of the pulmonary aspect of this disorder and need for early aggressive supportive treatment make identification crucial to patient management and prognostic counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 17 publications
1
35
0
2
Order By: Relevance
“…The mutation of FLNA has been shown to be associated with the neuronal migration, vascular function, connective tissue integrity, and skeletal development (Shelmerdine et al 2017); FLNA showed low expression in CRC patients and was significantly correlated with the incidence and development of CRC (Tian et al 2015). LBR, a transmembrane protein of the inner nuclear membrane, interacts with heterochromatin and B-type lamins through its nucleoplasmic aminoterminal domain and is phosphorylated throughout the cell cycle (Duband-Goulet et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The mutation of FLNA has been shown to be associated with the neuronal migration, vascular function, connective tissue integrity, and skeletal development (Shelmerdine et al 2017); FLNA showed low expression in CRC patients and was significantly correlated with the incidence and development of CRC (Tian et al 2015). LBR, a transmembrane protein of the inner nuclear membrane, interacts with heterochromatin and B-type lamins through its nucleoplasmic aminoterminal domain and is phosphorylated throughout the cell cycle (Duband-Goulet et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The Filamin A protein is an actin-binding and scaffolding protein that binds to integrins and also interacts with CFTR [27]. Of interest, mutations in the FLNA gene result in interstitial lung disease, a severe respiratory illness [28]. The FLNA protein is required for optimal T cell homing into lymph nodes and inflamed tissues [29].…”
Section: Plos Onementioning
confidence: 99%
“…There is emerging recognition of a respiratory phenotype of this genetic disorder that occurs in infancy and has unique features, including cardiovascular manifestations (aortic-valve disease and dilatation, patent ductus arteriosus, and pulmonary hypertension) and pulmonary manifestations (emphysema and lung cysts alternating with atelectasis and tracheobronchomalacia or stenosis). [14][15][16][17][18][19][20][21] A recent review summarizes the cases reported in the literature to date. 22 Thus far, at least 18 cases of FLNA-related disease with this respiratory phenotype have been identified in infancy.…”
Section: Connective-tissue Disordersmentioning
confidence: 99%
“…The respiratory phenotype of FLNArelated disease is now considered to be a childhood interstitial lung disease. 21 The filamin A protein is thought to be important in the maturation of alveoli in embryologic life, a process that affects lung growth and development. Findings similar to bronchopulmonary dysplasia due to alveolar simplification have been noted.…”
Section: Connective-tissue Disordersmentioning
confidence: 99%
See 1 more Smart Citation